Motoric cognitive risk syndrome in people with multiple sclerosis: prevalence and correlations with disease-related factors. (July 2022) - Dreyer-Alster, Sapir; Menascu, Shay; Aloni, Roy; Givon, Uri; Dolev, Mark; Achiron, Anat; Kalron, Alon
Background: The motoric cognitive risk (MCR) syndrome, defined as the coexistence of slow gait and subjective cognitive complaints, has as yet not been researched in people with multiple sclerosis (pwMS). Objective: To examine the prevalence of the MCR syndrome in pwMS and its association with disability, disease duration, perceived fatigue, and fear of falling. Methods: The study comprised 618 pwMS [43.7 (SD = 12.6) years, 61.7% females]. Gait speed was measured by the GAITRite™ electronic walkway (CIR Systems, Inc. Haverton, PA, USA). Cognitive status was defined according to the global cognitive score computed by the NeuroTrax™ cognitive battery (NeuroTrax Corporation, Medina, NY, USA). The sample was divided into four main groups: 'normal', 'cognitively impaired', 'gait impaired' or 'MCR'. Perceived fatigue was assessed by the Modified Fatigue Impact Scale; fear of falling by the Falls Efficacy Scale International. Results: Sixty-three (10.2%) patients were diagnosed with MCR. The percentage of subjects categorized as MCR was 26.0% in severely disabled pwMS compared with 10.9%, 6.0%, and 4.6% in moderately, mildly and very mildly disabled pwMS, respectively. Subjects in the MCR group presented with elevated fatigue compared with patients classified as normal [49.7 (SD = 23.3) vs 26.5 (SD = 19.2), p  < 0.001]. Fear of falling was significantly higher in the MCR and gait impairment groups compared with the cognitively impaired and normal groups. Conclusions: The current study corroborates the presence of MCR in pwMS. Nevertheless, future longitudinal research is warranted to better understand its application.